Quantum challenge-response identification using single qubit unitary operators - Choi, Ji-Woong; Kang, Min-Sung; Heo, Jino; Hong, Changho; Yoon, Chun-Seok; Han, Sang-Wook; Moon, Sung; Yang, Hyung-Jin (IOP PUBLISHING LTD, 2020)
In challenge-response authentication, the claimants are required to prove that they are legitimate users while minimizing the exposure of their confidential information. We propose a quantum challenge-response identification protocol using single qubit unitary operators that utilizes the mechanism of challenge-response, unlike most existing protocols that use (one-time) password authentication. We utilized the commutation relations of single qubit unitary operators to design this protocol that ensures the security of confidential information during identification in a quantum computing environment. For security analysis, we estimated the average fidelity of two quantum states after performing operations with the unitary operators based on the random numbers generated by two users. Subsequently, we evaluated the amount of information acquired by an eavesdropper to show that the proposed protocol is robust against impersonation and intercept-measurement attacks. Finally, we described the advantages of the protocol by comparing it with the existing quantum identification protocols.
Keywords: PING-PONG TECHNIQUE; IDENTITY AUTHENTICATION; TELEPORTATION; COMMUNICATION; PROTOCOL